Kukhar V. V., Glazko V. V., Anishсhenko А. S. Development of a general method for calculating of matrix elastomeric compensators of cord type for reducing errors in the "press-die" system. - Кухарь, В. В.; Глазко, В. В.; Анищенко, А. С. (Problems of Tribology, 2018)
The errors of the "press-die" system are considered. A brief review of the existing designs of the error compensators of the "press-die" system is made. The main advantages of matrix elastomeric compensators of cord type with respect to other types of compensators are revealed. The mission of the work is the development of a general methodology for calculating of matrix elastomeric compensators of cord type. A comparative analysis of the applicable methods for calculating the parameters of the stress-strain state of the compensator is made. An optimal method for existing production conditions has been identified. The method of eccentric compression of a bar is recognized as the optimal method of verification calculation. The necessary assumptions in the calculation and the available initial data were formulated. The method of verification calculation is developed. Directions for further development of research have been determined. The shortcomings of the existing design of the elastomeric matrix elastomer compensator of the cord type and ways to improve it are analyzed. The main drawback of the patented design is the presence of pin-type base elements, between which an elastomeric element is laid. This narrows the possibility of reconfiguration and limits the permissible movement (compression) of rigid base plates in the direction of applying the load. One way of improving the structure under consideration is the use of non-polymerizable adhesive substances for horizontal based elastomer instead basing interdigital elements. The second way to improve is to use a cord with magnetic properties. In the material of such a cord, the magnetic powder must be uniformly distributed. In addition, it is proposed to change the circular cross-section of the elastomeric element to a square one. This will increase the initial support area of the elastomeric element and stabilize the elastic properties of the compensator when the workload is applied. As a result of the conducted researches, the method of verification calculation of a matrix elastomeric compensator of cord type was proposed; the need for automation of calculations is justified; directions of perfection of designs of elastomeric compensators of a cord type are revealed.